Hole transport layer precursor solution, solar cell and method for preparing solar cell
By using the hole transport layer precursor solution of carbazoles and organic iodine salts in perovskite solar cells, the problem of self-assembly layer preparation and the problem of easy desorption at high temperatures is solved, efficient and stable hole transmission is achieved, and the photoelectric conversion efficiency of solar cells is significantly improved.
Patent Information
- Application Number
- CN202411954992.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, self-assembled hole transport layer has preparation problems in large-area photovoltaic modules and large-scale production, and is prone to desorption under high temperature conditions, affecting the photoelectric conversion efficiency of solar cells.
A hole transport layer precursor solution is provided, including carbazole hole transport material and organic iodine salt, and the hole transport layer is prepared by a wet processing process to improve film thickness control and mechanical and thermal stability.
It significantly improves the photoelectric conversion efficiency of perovskite solar cells, improves the stability and scalability of the hole transport layer, and supports the industrial application of perovskite photovoltaic technology.
Smart Images

Figure BDA0005215599560000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of solar cells, and in particular to a hole transport layer precursor solution, a solar cell and a method for preparing the solar cell. Background Art
[0002] Over the past decade, perovskite solar cells have rapidly emerged as a bright new star in the photovoltaic field due to their unique performance advantages, such as flexible bandgap regulation, excellent light absorption efficiency, and efficient carrier transport characteristics. These characteristics work together to make the photoelectric conversion efficiency of Feide perovskite solar cells soar, significantly surpassing the efficiency of traditional solar cell technology.
[0003] In the structural design of perovskite solar cells, the trans configuration is favored due to its excellent performance. Trans-structured perovskite cells are mainly composed of transparent electrodes, hole transport layers, perovskite light absorption layers, electron transport layers and metal back electrodes. In order to improve the efficiency of cells, researchers widely use carbazole derivatives to form a hole transport layer through self-assembly, because carbazole molecules can form a highly ordered monolayer, which effectively promotes the transport of holes.
[0004] However, the challenge of the traditional method of preparing self-assembled hole transport layers is that the self-assembled layer, as a single molecular layer, mainly relies on the spin coating process to prepare it, which limits its application in large-area photovoltaic modules and faces technical difficulties in large-scale production; secondly, because the self-assembled layer is composed of small molecules, when the battery operates under light conditions and the temperature rises, these small molecules are prone to desorption, thereby damaging the photoelectric conversion efficiency of the solar cell.
[0005] Therefore, developing new hole transport layer materials and preparation processes to overcome the limitations of the self-assembled layer and improve the efficiency and stability of perovskite solar cells in practical applications has become a hot topic and key direction of current research. This requires not only solving the innovation of material formulations, but also taking into account the scalability of the process and the needs of large-scale production to ensure the commercial feasibility of perovskite solar cell technology. Summary of the invention
[0006] The main purpose of the present invention is to provide a hole transport layer precursor solution, a solar cell and a method for preparing a solar cell, so as to solve the problem that the hole transport layer materials and preparation processes in the prior art cannot meet the efficiency requirements of perovskite solar cells in practical applications.
[0007] To achieve the above object, according to one aspect of the present invention, a hole transport layer precursor solution is provided, comprising a carbazole hole transport material, an organic ammonium iodide salt and a solvent, wherein the organic ammonium iodide salt is selected from alkyl ammonium iodide and / or aromatic ammonium iodide.
[0008] Furthermore, in the above-mentioned hole transport layer precursor solution, the carbazole-based hole transport material includes one of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid, 4-cyano-3,6-di(4-cyanophenyl)-9H-carbazole, 4,4'-diamino-2,2'-bicarbazole and 4,4',4"-tri(methylcyclohexyl)-triphenylamine, or any combination thereof.
[0009] Furthermore, in the above-mentioned hole transport layer precursor solution, the alkyl ammonium iodide includes a straight-chain alkyl ammonium iodide of 4-15 carbon atoms; preferably, the alkyl ammonium iodide includes one of n-butyl ammonium iodide, n-pentyl ammonium iodide, n-hexyl ammonium iodide, n-octyl ammonium iodide, n-decyl ammonium iodide, n-dodecyl ammonium iodide, n-tetradecyl ammonium iodide and n-hexadecyl ammonium iodide, or any combination thereof.
[0010] Further, in the above-mentioned hole transport layer precursor solution, the aromatic iodinated amine includes substituted or unsubstituted phenyl iodinated amine; preferably, the aromatic iodinated amine includes phenyl iodinated amine, 4-fluorophenyl iodinated amine, 3-fluorophenyl iodinated amine, 2-fluorophenyl iodinated amine, 4-cyanophenyl iodinated amine, 4-methylphenyl iodinated amine, 4-ethylphenyl iodinated amine, phenethyl iodinated amine, 4-fluorophenethyl iodinated amine, 3-fluorophenethyl iodinated amine, 2-fluorophenethyl iodinated amine, 4-chlorophenethyl iodinated amine and 4-methoxyphenethyl iodinated amine or any combination thereof.
[0011] Furthermore, in the hole transport layer precursor solution, the weight ratio of the carbazole hole transport material to the organic iodine ammonium salt is between 1:10 and 10:1, preferably between 1:4 and 4:1, and more preferably between 1:2 and 2:1.
[0012] Furthermore, in the above-mentioned hole transport layer precursor solution, the solvent is selected from one of methanol, ethanol, isopropanol, n-propanol, butanol, ethylene glycol, ethyl acetate, ethyl propionate, acetone, methyl ethyl ketone, acetonitrile, propionitrile, toluene, xylene, dimethylformamide and dimethyl sulfoxide, or any combination thereof.
[0013] Furthermore, in the above-mentioned hole transport layer precursor solution, based on the total volume of the solvent in the hole transport layer precursor solution, the total concentration of the carbazole hole transport material and the organic iodine ammonium salt is in the range of 0.1 mg / ml to 1 mg / ml, preferably in the range of 0.2 mg / ml to 0.8 mg / ml.
[0014] According to another aspect of the present invention, a solar cell is provided, comprising the following layers: a transparent electrode layer; a hole transport layer; a perovskite layer; an electron transport layer; and a back electrode layer, wherein the hole transport layer is prepared from a hole transport layer precursor solution according to the present invention.
[0015] According to another aspect of the present invention, a method for preparing the solar cell of the present invention is provided, comprising the following steps: step S1, dissolving a carbazole hole transport material and an organic iodine ammonium salt in a solvent to obtain a hole transport layer precursor solution; step S2, coating the hole transport layer precursor solution on a transparent electrode layer using a wet processing technology to obtain a hole transport layer; step S3, preparing a perovskite layer on the hole transport layer; step S4, preparing an electron transport layer on the perovskite layer; step S5, preparing a back electrode layer on the electron transport layer.
[0016] Furthermore, in the above method, the wet processing technology is blade coating, wire rod coating or slot coating.
[0017] Furthermore, in the above method, the hole transport layer precursor solution is coated on the transparent electrode layer using wire bar coating, and the coating thickness of the hole transport layer is in the range of 10 μm to 200 μm, preferably in the range of 30 μm to 120 μm; the coating speed is in the range of 2 mm / s to 50 mm / s, preferably in the range of 3 mm / s to 20 mm / s.
[0018] Further, in the above method, step S3 further includes applying a perovskite layer precursor onto the hole transport layer using slit coating, wherein the perovskite layer precursor includes a perovskite crystal with a structure of ABX3, wherein A is CH3NH3, NH2CHNH2, C8H9NH3 or Cs, B is Pb or Sn, and X is Cl, Br, I or a halide; the coating thickness of the perovskite layer is in the range of 200nm to 1000nm, preferably in the range of 300nm to 600nm.
[0019] Further, in the above method, step S4 further includes using vacuum thermal evaporation to form an electron transport layer precursor on the perovskite layer, the electron transport layer precursor includes one of fullerene, titanium dioxide, zinc oxide, tin oxide and zirconium oxide or any combination thereof, and the coating thickness of the electron transport layer is in the range of 10nm to 100nm, preferably in the range of 3nm to 80nm. Preferably, step S4 also includes after forming the electron transport layer, using vacuum thermal evaporation to form a modification layer on the electron transport layer, the modification layer includes one of bathocuproine, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, 4,4'-dicyano-2,2'-biphenyl and 3-(4-tert-butylphenyl)-2-methyl-4,5-dicyano-1,3,4-oxadiazine or any combination thereof, and the coating thickness of the modification layer is in the range of 2nm to 10nm, preferably in the range of 3nm to 8nm.
[0020] Furthermore, in the above method, step S4 further includes a reactive plasma deposition process to deposit tungsten indium oxide on the electron transport layer to form a back electrode layer, and the coating thickness of the back electrode layer is in the range of 100nm to 300nm, preferably in the range of 120nm to 200nm.
[0021] The application of the technical solution of the present invention can solve the limitations of the preparation of self-assembled layers in the prior art, and also significantly improve the photoelectric conversion efficiency of perovskite solar cells, providing important technical support for the industrial application of perovskite photovoltaic technology. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments. The following embodiments are merely exemplary and do not constitute a limitation on the scope of protection of the present invention.
[0023] As described in the background technology, the hole transport layer materials and preparation processes in the prior art cannot meet the efficiency requirements of perovskite solar cells in practical applications. In view of the problems in the prior art, a typical embodiment of the present invention provides a hole transport layer precursor solution. The hole transport layer precursor solution comprises a carbazole hole transport material, an organic iodine ammonium salt and a solvent. In the hole transport layer precursor solution of the present invention, the organic iodine ammonium salt is selected from alkyl ammonium iodide and / or aromatic iodine amine.
[0024] In the hole transport layer precursor solution of the present invention, the hole transport material is preferably selected from carbazole compounds, which are widely used in perovskite solar cells due to their excellent hole transport ability and good chemical stability. Organic ammonium iodide salts, as another key component of the present invention, are mainly divided into two categories: alkyl ammonium iodide and aromatic iodine amine. Organic ammonium iodide salts can not only serve as bottom interface passivators, but also synergistically act with carbazole hole transport materials to optimize the performance of the transport layer.
[0025] By adding organic iodine ammonium salt to the carbazole hole transport material liquid, the present invention effectively solves the limitations of the self-assembled layer preparation, improves the film thickness control range of the hole transport layer, and enhances the mechanical stability and thermal stability of the film. The perovskite photovoltaic module using the formula of the present invention has a significant improvement in photoelectric conversion efficiency, up to 17.8%. This shows that the technical solution of the present invention not only optimizes the preparation of the hole transport layer, but also significantly improves the performance of the entire module through bottom interface passivation.
[0026] In summary, the present invention not only solves the limitations of the preparation of self-assembled layers in the prior art by providing a precursor solution containing a carbazole-type hole transport material and an organic iodine ammonium salt, but also significantly improves the photoelectric conversion efficiency of perovskite solar cells, providing important technical support for the industrial application of perovskite photovoltaic technology.
[0027] In some embodiments of the present invention, the carbazole hole transport material in the hole transport layer precursor solution includes one of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid, 4-cyano-3,6-di(4-cyanophenyl)-9H-carbazole, 4,4'-diamino-2,2'-bicarbazole and 4,4',4"-tri(methylcyclohexyl)-triphenylamine, or any combination thereof.
[0028] Carbazole hole transport materials are ideal for hole transport layers in perovskite solar cells due to their unique properties. Carbazole compounds, with their π-conjugated system and good charge transport ability, are widely used in organic electronic devices, especially as efficient hole transport layer materials in perovskite solar cells. In the present invention, carbazole hole transport materials that can be used in different embodiments include but are not limited to: [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz), 4-cyano-3,6-di(4-cyanophenyl)-9H-carbazole, 4,4'-diamino-2,2'-bicarbazole, 4,4',4"-tri(methylcyclohexyl)-triphenylamine. [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz) contains two methoxy groups and one phosphate group, which can effectively promote the transport of holes, while providing additional passivation, reducing non-radiative recombination, and improving battery stability. Me-4PACz enhances the interaction with the substrate through its butyl chain. , which helps to form a tighter hole transport interface and reduce contact resistance, thereby improving the photoelectric conversion efficiency. The cyano and phenyl groups in 4-cyano-3,6-di(4-cyanophenyl)-9H-carbazole provide the material with good photothermal stability and enhance the electron acceptance ability, making the material have excellent performance in the hole transport layer. 4,4'-Diamino-2,2'-bicarbazole can effectively promote the transport of holes through the dicarbazole structure and amino group. At the same time, the presence of amino group helps to improve the solubility of the material and the interfacial compatibility with other layers. The triphenylamine structure of 4,4',4"-tri(methylcyclohexyl)-triphenylamine provides a large π-conjugated system, thereby enhancing the hole transport ability, while the methylcyclohexyl group increases the thermal stability and mechanical strength of the material, allowing it to maintain good performance under high temperature and stress conditions.
[0029] In the present invention, the above-mentioned carbazole hole transport materials can be used alone or in any combination to meet specific performance requirements. For example, the combination of MeO-2PACz and Me-4PACz can optimize the conductivity and stability of the transport layer by adjusting their ratio, thereby achieving optimal performance under different battery conditions. In addition, the combination of carbazole materials and organic iodine ammonium salts can further improve the interface contact and enhance the passivation effect of the hole transport layer. By dissolving these materials in a suitable solvent to form a stable and easy-to-apply precursor solution, various wet processing techniques such as blade coating, wire rod coating, slit coating, etc. can be used to prepare a uniform, quality-controlled hole transport layer. This combination not only improves the flexibility of preparation, but also significantly improves the photoelectric conversion efficiency and long-term stability of perovskite cells, providing strong technical support for the development and industrial production of high-performance perovskite cells.
[0030] In some embodiments of the present invention, the alkyl ammonium iodide includes a linear alkyl ammonium iodide of 4-15 carbon atoms; preferably, the alkyl ammonium iodide includes one of n-butyl ammonium iodide, n-pentyl ammonium iodide, n-hexyl ammonium iodide, n-octyl ammonium iodide, n-decyl ammonium iodide, n-dodecyl ammonium iodide, n-tetradecyl ammonium iodide and n-hexadecyl ammonium iodide or any combination thereof. The alkyl ammonium iodide used in the present invention is a class of organic iodine salt compounds containing linear alkyl groups, and the length of the alkyl chain is between 4 and 15 carbon atoms. Such compounds have good solubility and are easy to mix with carbazole hole transport materials to form a stable solution. At the same time, they can form a protective film at the interface of the perovskite and the hole transport layer by self-assembly, effectively passivating the defects on the surface of the perovskite, reducing non-radiative recombination, thereby improving the photoelectric conversion efficiency and stability of the device.
[0031] n-Butylammonium iodide (C4H9NH3I) has a shorter alkyl chain and is easy to form a dense self-assembled monolayer on the surface of perovskite, which has a significant effect on improving the uniformity of the hole transport layer and reducing the defect density. n-Hexylammonium iodide (C6H 15 NH3I) and n-octylammonium iodide (C8H 19 The alkyl chain length of n-dodecyl ammonium iodide (NH3I) is moderate, which can provide sufficient physical isolation while maintaining good solubility and self-assembly properties, reducing the non-radiative recombination between charge carriers and the perovskite lattice. 12 H 27 NH3I), n-tetradecyl ammonium iodide (C 14 H 31 NH3I) and hexadecyl ammonium iodide (C 16 H 37NH3I) provides additional physical stability and interface regulation capabilities through its longer alkyl chain, which is particularly suitable for perovskite cells that require enhanced mechanical and thermal stability.
[0032] In practical applications, the alkyl ammonium iodides described above can be used alone or in any combination to meet the needs of different perovskite materials and battery structures. For example, the mixture of n-butyl ammonium iodide and n-octadecyl ammonium iodide can combine the interface passivation ability of the short alkyl chain and the physical stability of the long alkyl chain to prepare a perovskite solar cell with more balanced performance.
[0033] In some embodiments of the present invention, the aromatic iodinated amine includes substituted or unsubstituted phenyl iodinated amine; preferably, the aromatic iodinated amine includes phenyl iodinated amine, 4-fluorophenyl iodinated amine, 3-fluorophenyl iodinated amine, 2-fluorophenyl iodinated amine, 4-cyanophenyl iodinated amine, 4-methylphenyl iodinated amine, 4-ethylphenyl iodinated amine, phenethyl iodinated amine, 4-fluorophenethyl iodinated amine, 3-fluorophenethyl iodinated amine, 2-fluorophenethyl iodinated amine, 4-chlorophenethyl iodinated amine and 4-methoxyphenethyl iodinated amine, or any combination thereof.
[0034] Aromatic iodinated amines are another key additive used in the present invention to improve the performance of perovskite solar cells. Aromatic iodinated amines, especially phenyl iodinated amines and their derivatives, have aromatic ring structures and iodinated amine groups, and can improve the interfacial properties of perovskite materials through various approaches. The introduction of phenyl iodinated amines (PEAI) can form coordination bonds with unpaired cations on the surface of perovskite materials, thereby passivating surface defects, reducing non-radiative recombination, and improving the stability and photoelectric conversion efficiency of the device. In addition, the aromatic rings in phenyl iodinated amines can also enhance the intermolecular interaction with carbazole hole transport materials through π-π stacking, promoting the formation of a more uniform and stable transport layer. The present invention particularly preferred aromatic iodine amine includes phenyl iodine amine (PEAI), 4-fluorophenyl iodine amine (pF-PEAI), 3-fluorophenyl iodine amine (mF-PEAI), 2-fluorophenyl iodine amine (oF-PEAI), 4-cyanophenyl iodine amine, 4-methylphenyl iodine amine, 4-ethylphenyl iodine amine, phenethyl iodine amine, 4-fluorophenethyl iodine amine, 2-fluorophenethyl iodine amine, 4-chlorophenethyl iodine amine and 4-methoxyphenethyl iodine amine. These compounds are through different substituent groups on the phenyl ring, such as fluorine, cyanide, methyl, ethyl, chlorine and methoxy, show different physical and chemical properties, so as to provide the passivation effect of optimization under different conditions. For example, 4-fluorophenyl iodine amine (pF-PEAI) can enhance the polarity and stability of the molecule by introducing fluorine atoms, and simultaneously due to the interaction of fluorine atoms with the surface of perovskite materials, can more effectively passivate defects, improve the photoelectric performance of the device. 4-Methoxyphenethylamine iodide improves the solubility of the material in organic solvents through its hydrophobic methoxy group, which is beneficial to solution preparation and wet processing. At the same time, the presence of methoxy groups at the interface helps reduce the penetration of water and oxygen and enhances the environmental stability of the battery.
[0035] In different embodiments of the present invention, aromatic iodinated amines can be used alone or in combination with other aromatic iodinated amines or alkyl ammonium iodides to meet specific performance requirements and preparation conditions. For example, the combined use of MeO-2PACz and PEAI, mF-PEAI can optimize the passivation effect of the transport layer, and by controlling the ratio of different materials, the physical and chemical properties of the transport layer can be adjusted to meet the requirements of different perovskite materials and battery structures.
[0036] Furthermore, by mixing 4-fluorophenylamine iodide with 4-methylphenylamine iodide, it is possible to introduce additional electron blocking functions while maintaining good interface passivation capabilities, thereby improving the efficiency and stability of the hole transport layer. In addition, the combination of different fluorinated derivatives, such as pF-PEAI with mF-PEAI or oF-PEAI, can utilize the different spatial arrangements of fluorine atoms to improve the comprehensive performance of the material, including improving the compatibility of the perovskite / transport layer interface, enhancing the stability of the film layer, and improving the overall photoelectric conversion efficiency.
[0037] In a further embodiment, the weight ratio of the carbazole hole transport material to the organic ammonium iodide salt is between 1:10 and 10:1, preferably between 1:4 and 4:1, and more preferably between 1:2 and 2:1. In the technical solution of the present invention, the weight ratio of the carbazole hole transport material (such as MeO-2PACz, Me-4PACz, etc.) to the organic ammonium iodide salt (including alkyl ammonium iodide and aromatic iodide) is set in a wide range, i.e., 1:10 to 10:1. Within this range, the preparer can adjust the relative content of the material according to different application scenarios, battery structures and target performance.
[0038] At low ratios (e.g., 1:10), the content of organic iodine ammonium salt is high, which is conducive to forming a thicker passivation layer between the perovskite layer and the hole transport layer, reducing interface defects, thereby improving the photoelectric conversion efficiency and stability of the battery. However, too high an organic iodine ammonium salt ratio (exceeding the scope of the present invention) may affect the hole transport capacity of the hole transport layer, resulting in a reduction in the transfer efficiency of charge carriers inside the device, thereby affecting the overall performance. On the contrary, when the ratio of carbazole hole transport materials is high, such as 10:1, the transfer capacity of the hole transport layer is enhanced, which is conducive to improving the hole collection efficiency in the photoelectric conversion efficiency. But too high a ratio (exceeding the scope of the present invention) may weaken the passivation effect, especially for the defect passivation ability on the interface, thereby adversely affecting the long-term stability of the battery.
[0039] In order to balance the hole transport capacity and the interface passivation effect, the present invention preferably controls the weight ratio within the range of 1:10 to 10:1, preferably within the range of 1:4 to 4:1. Within the above range, the interaction between the carbazole hole transport material and the organic iodine ammonium salt is the most coordinated, which not only ensures the good conductivity of the hole transport layer, but also makes full use of the passivation effect of the organic iodine ammonium salt, thereby achieving the best balance between photoelectric conversion efficiency and stability.
[0040] More preferably, the weight ratio is determined to be in the range of 1:2 to 2:1 as the optimal interval. Within this range, the ratio of MeO-2PACz or Me-4PACz to materials such as n-octylammonium iodide and PEAI can ensure that the photoelectric conversion efficiency of the perovskite battery module under standard test conditions is significantly improved, with the highest efficiency reaching 17.8%. In addition, this ratio can also improve the tolerance of the hole transport layer to the film thickness, making it possible to prepare large-area continuous thin films using wet processing techniques such as blade coating, wire rod coating, and slit coating, laying the foundation for the industrial production of perovskite solar cells.
[0041] In an embodiment of the present invention, the solvent is selected from one of methanol, ethanol, isopropanol, n-propanol, butanol, ethylene glycol, ethyl acetate, ethyl propionate, acetone, methyl ethyl ketone, acetonitrile, propionitrile, toluene, xylene, dimethylformamide and dimethyl sulfoxide or any combination thereof. In the preparation process of the perovskite solar cell of the present invention, the choice of solvent has a crucial influence on the stability and film-forming performance of the hole transport layer precursor solution.
[0042] The solvents in the present invention include, but are not limited to, methanol, ethanol, isopropanol, n-propanol, butanol, ethylene glycol, ethyl acetate, ethyl propionate, acetone, methyl ethyl ketone, acetonitrile, propionitrile, toluene, xylene, dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). These solvents are all green solvents that can well dissolve carbazole hole transport materials and organic iodine ammonium salts, and their selection is based on their respective solubility, volatility, polarity and compatibility with materials.
[0043] Methanol and ethanol, due to their high polarity and good solubility, can effectively dissolve carbazole compounds and organic iodine ammonium salts, and evaporate quickly, which helps to form a uniform and dense hole transport layer. Isopropyl alcohol and n-propyl alcohol, due to their lower polarity and higher boiling point, can provide a milder solvent environment, which is conducive to controlling the film formation process and avoiding film defects caused by rapid volatilization. Ethylene glycol and ethyl acetate, etc., through their specific chemical structure, improve the solubility of the material and the stability of the solution, and help to form a precursor solution with good viscosity and fluidity, which is suitable for wet processing such as wire rod coating and slit coating. In addition, solvents such as acetone, methyl ethyl ketone, acetonitrile and propionitrile can accelerate the film drying process, reduce processing time and improve production efficiency due to their low viscosity and high volatility. Toluene and xylene, through their hydrophobicity and low polarity, reduce the water content in the solution, help to form a more stable perovskite structure, thereby improving the photoelectric conversion efficiency and long-term stability of the battery. Dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) are highly polar aprotic solvents with good solubility and low volatility. They can provide a stable solution environment and are suitable for preparation processes that require precise control of the film-forming process, such as slit coating and inkjet printing.
[0044] It is noteworthy that the present invention is not limited to the use of a single solvent, but can adopt any combination of solvents. By mixing solvents of different properties, the advantages of various solvents can be combined to accurately adjust the viscosity, fluidity and evaporation rate of the solution to adapt to different preparation processes and material requirements, and to achieve the best film quality. For example, methanol and ethanol are mixed in a certain proportion, solubility and volatility can be balanced, which helps to form a uniform film. And acetone is mixed with toluene, while reducing the film formation time, the water content in the solution can be reduced, and the crystallization quality of the perovskite material and the stability of the hole transport layer can be improved. The combined use of DMF and DMSO can control the film growth rate by adjusting the ratio while maintaining the stability of the solution, which is particularly important for preparing high-quality, large-area perovskite photovoltaic modules.
[0045] In a further embodiment, based on the total volume of the solvent in the hole transport layer precursor solution, the total concentration of the carbazole hole transport material and the organic iodine ammonium salt is in the range of 0.1 mg / ml to 1 mg / ml, preferably in the range of 0.2 mg / ml to 0.8 mg / ml. The concentration of the precursor solution is an important parameter in the preparation of perovskite solar cells, which directly affects the film thickness and uniformity of the hole transport layer and the photoelectric performance of the final device.
[0046] In the method for preparing perovskite solar cells of the present invention, the total concentration of carbazole hole transport materials (such as MeO-2PACz, Me-4PACz) and organic ammonium iodide salts (such as n-octylammonium iodide, PEAI and its derivatives) is set in the range of 0.1 mg / ml to 1 mg / ml. The selection of this concentration range is based on a comprehensive consideration of film quality and battery performance. Too low a concentration (lower than 0.1 mg / ml) may cause the hole transport layer to be too thin, affecting the effective transport of charge carriers and the interface passivation effect; while too high a concentration (higher than 1 mg / ml) may cause uneven coating due to excessive viscosity of the solution, and even form a discontinuous or too thick film layer, thereby affecting the photoelectric conversion efficiency and stability of the battery.
[0047] In order to obtain the best hole transport layer performance, the present invention preferably controls the total concentration within the range of 0.2 mg / ml to 0.8 mg / ml. In this range, the viscosity and fluidity of the solution are optimized, which not only ensures the feasibility of wet processing technology (such as blade coating, wire rod coating, slit coating, etc.), but also ensures the continuity and uniformity of film formation, thereby improving the charge transfer efficiency of the hole transport layer and the passivation effect on the perovskite interface.
[0048] In another typical embodiment of the present application, a solar cell is provided, which includes a transparent electrode layer, a hole transport layer, a perovskite layer, an electron transport layer and a back electrode layer, wherein the hole transport layer is prepared from the hole transport layer precursor solution described above.
[0049] The transparent electrode layer, as the front electrode of the battery, is mainly composed of transparent conductive glass (such as FTO or ITO). It has high light transmittance and good electrical conductivity to ensure that sunlight can effectively penetrate into the battery, and at the same time can guide the generated holes to achieve the output of electrical energy. In some embodiments of the present invention, the transparent electrode layer uses FTO glass, which can be pre-treated, including ultrasonic cleaning and ultraviolet cleaning, to ensure the cleanliness of the surface, thereby improving the contact quality between the subsequent layer and the transparent electrode layer.
[0050] The hole transport layer of the solar cell is prepared from the hole transport layer precursor solution described above, which contains carbazole hole transport materials (such as MeO-2PACz, Me-4PACz) and organic ammonium iodide salts (such as n-octylammonium iodide, PEAI and its derivatives). The function of the hole transport layer is to collect and transport holes generated from the perovskite layer, while passivating the interface and reducing non-radiative recombination losses. By adopting a wet processing technology (such as wire rod coating), this layer can achieve efficient passivation of the perovskite layer while maintaining good charge transfer efficiency, significantly improving the photoelectric conversion efficiency and stability of the battery. In an embodiment of the present invention, the thickness of the hole transport layer is in the range of 10μm to 200μm. In different embodiments of the present invention, the thickness of the hole transport layer is in the following range: 10 μm to 200 μm, 20 μm to 190 μm, 30 μm to 180 μm, 40 μm to 170 μm, 50 μm to 160 μm, 60 μm to 150 μm, 70 μm to 140 μm, 80 μm to 130 μm, 90 μm to 120 μm, 100 μm to 110 μm, 50 μm to 200 μm, 100 μm to 200 μm, 150 μm to 200 μm, 10 μm to 150 μm, 10 μm to 100 μm or 10 μm to 50 μm.
[0051] In the solar cell of the present invention, the perovskite layer is used as the light absorption layer of the cell, and its structure is generally a perovskite crystal of ABX3, wherein A is CH3NH3, NH2CHNH2, C8H9NH3 or Cs, B is Pb or Sn, and X is Cl, Br, I or a halide. In the present invention, the thickness of the perovskite layer is in the range of 200nm to 1000nm to ensure optimal light absorption and charge separation. In different embodiments of the present invention, the thickness of the perovskite layer is in the following range: 200nm to 1000nm, 300nm to 900nm, 400nm to 800nm, 500nm to 700nm, 200nm to 900nm, 200nm to 800nm, 200nm to 700nm, 200nm to 600nm, 200nm to 500nm, 200nm to 400nm, 200nm to 300nm, 300nm to 1000nm, 400nm to 1000nm, 500nm to 1000nm, 600nm to 1000nm, 700nm to 1000nm or 800nm to 1000nm.
[0052] The electron transport layer is located between the perovskite layer and the back electrode layer, and is mainly composed of materials such as fullerene (C60), which is applied by vacuum thermal evaporation, and its thickness is in the range of 200nm to 1000nm. The electron transport layer is responsible for collecting and exporting the electrons generated by the perovskite layer, and together with the hole transport layer, ensures efficient separation and transmission of charge carriers. In different embodiments of the present invention, the thickness of the electron transport layer is in the following range: 200nm to 1000nm, 300nm to 900nm, 400nm to 800nm, 500nm to 700nm, 200nm to 900nm, 200nm to 800nm, 200nm to 700nm, 200nm to 600nm, 200nm to 500nm, 200nm to 400nm, 200nm to 300nm, 300nm to 1000nm, 400nm to 1000nm, 500nm to 1000nm, 600nm to 1000nm, 700nm to 1000nm or 800nm to 1000nm.
[0053] The back electrode layer serves as the rear electrode of the battery and is arranged on the other side of the electron transport layer. The back electrode layer can be in the form of tungsten-doped indium oxide (IWO) and is prepared by reactive plasma deposition (RPD) technology. The thickness of the back electrode layer is in the range of 100nm to 300nm, preferably in the range of 120nm to 200nm. The back electrode layer not only has good electrical conductivity, but also has good contact with the electron transport layer. In different embodiments of the present invention, the thickness of the back electrode layer is in the following range: 100nm to 300nm, 120nm to 280nm, 140nm to 260nm, 160nm to 240nm, 180nm to 220nm, 120nm to 300nm, 140nm to 300nm, 160nm to 300nm, 180nm to 300nm, 200nm to 300nm, 220nm to 300nm. m, 240nm to 300nm, 260nm to 300nm, 280nm to 300nm, 100nm to 280nm, 100nm to 260nm, 100nm to 240nm, 100nm to 220nm, 100nm to 200nm, 100nm to 180nm, 100nm to 160nm, 100nm to 140nm, 100nm to 120nm or 120nm to 200nm.
[0054] The solar cell prepared by using the hole transport layer precursor solution proposed by the present invention significantly improves the photoelectric conversion efficiency of the solar cell. The perovskite solar cell based on the hole transport layer of the present invention not only performs well in photoelectric conversion efficiency, but also has higher long-term stability and can withstand more complex and harsh external environments. The solar cell of the present invention constructs a multilayer structure with high photoelectric conversion efficiency and long-term stability by combining the hole transport layer with the perovskite layer, the electron transport layer and the back electrode layer.
[0055] In another typical embodiment of the present invention, a method for a solar cell of the present invention is provided. The method comprises the following steps: step S1, dissolving a carbazole hole transport material and an organic iodine ammonium salt in a solvent to obtain a hole transport layer precursor solution; step S2, coating the hole transport layer precursor solution on a transparent electrode layer using a wet processing process to obtain a hole transport layer; step S3, preparing a perovskite layer on the hole transport layer; step S4, preparing an electron transport layer on the perovskite layer; step S5, preparing a back electrode layer on the electron transport layer.
[0056] The present invention provides a method for preparing a high-performance perovskite solar cell, which aims to improve the photoelectric conversion efficiency and long-term stability of the battery by optimizing the formula and preparation process of the hole transport layer. In step S1, a hole transport layer precursor solution is first prepared. Carbazole hole transport materials (such as carbazole compounds such as MeO-2PACz, Me-4PACz) and organic iodine ammonium salts (including alkyl ammonium iodide and aromatic iodine amines and their derivatives, such as n-octyl ammonium iodide, PEAI and its fluorinated derivatives) are dissolved in a solvent. The choice of solvent needs to be based on its solubility, volatility, polarity and compatibility with the material. Ideal solvents include but are not limited to ethanol, methanol, isopropanol, etc. The total concentration of the solution is controlled within a preferred range of 0.2 mg / ml to 0.8 mg / ml to ensure the stability of the solution and facilitate the subsequent coating process. The hole transport layer precursor solution obtained by step S1 can not only improve the interface passivation effect, but also optimize the charge transfer capacity.
[0057] Next, in step S2, the hole transport layer precursor solution obtained in step S1 is coated on the transparent electrode layer. The precursor solution obtained in step S1 can be coated on a transparent electrode layer (such as FTO or ITO conductive glass) using a wet processing process. The wet processing process may include any coating method known in the art, wherein wire rod coating is preferably used in the present invention because it can provide a uniform coating thickness, preferably in the range of 30 μm to 120 μm, and can provide good film quality. The coating speed is preferably in the range of 3 mm / s to 20 mm / s, and the solution dosage is preferably in the range of 300 μl to 600 μl, so that the ideal film thickness can be effectively controlled. After the coating is completed, it is necessary to perform an annealing treatment at a temperature of about 100 ° C for 10 minutes to promote the self-assembly of the material and form a stable hole transport layer.
[0058] A perovskite layer is formed on the hole transport layer prepared in step S2. The perovskite layer precursor solution can be prepared by slit coating or spin coating, and then annealed, for example, at a temperature of about 150° C. for 30 minutes, to promote the formation of perovskite crystals. The thickness of the perovskite layer is preferably in the range of 300 nm to 600 nm to ensure optimal light absorption and charge separation capabilities.
[0059] After the preparation of the perovskite layer is completed, an electron transport material such as fullerene (C60) or metal oxides TiO2, ZnO, etc. can be deposited on the perovskite layer by a vacuum thermal evaporation process. The thickness of the electron transport layer is preferably in the range of 30nm to 80nm to ensure the effective collection and extraction of electrons while avoiding negative impacts on the light absorption of the battery. After the electron transport layer is prepared, a layer of modifying material such as BCP can be further deposited to improve the contact quality between the electron transport layer and the back electrode layer and reduce interface recombination losses.
[0060] Finally, tungsten-doped indium oxide (IWO) is deposited on the electron transport layer to form a back electrode layer. The back electrode layer can be formed by reactive plasma deposition (RPD) technology. The thickness of the IWO layer is preferably in the range of 120nm to 200nm to ensure good electrical conductivity and mechanical stability.
[0061] The perovskite solar cells prepared through the above steps not only perform well in photoelectric conversion efficiency, but also have higher long-term stability and environmental adaptability.
[0062] In a preferred embodiment, the coating of the hole transport layer precursor solution can be implemented in step S2 by blade coating, wire rod coating or slit coating. Blade coating is a highly flexible and cost-effective coating technique that adjusts the thickness of the coating by controlling the gap between the blade and the substrate, and is suitable for a variety of scales from laboratory to industrial production. In the present invention, the hole transport layer is prepared by blade coating, and the operator can adjust the gap between the blade and the substrate to a range of 10-200 μm, preferably 30-120 μm, according to the required coating thickness, to achieve the desired film thickness and coating uniformity. In addition, the speed of blade coating can be in the range of 2-50 mm / s, preferably 3-20 mm / s, and the appropriate coating speed can ensure that the solution is evenly distributed on the substrate to avoid uneven coating or defects. Another advantage of the blade coating process is that it can handle precursor solutions of various viscosities, so it is particularly suitable for the hole transport layer precursor solution containing complex components in the present invention, and can prepare a high-quality hole transport layer, which lays a good foundation for the preparation of subsequent perovskite layers and electron transport layers.
[0063] In other embodiments, wire bar coating can be used, which is particularly suitable for preparing uniform thin films that require precise thickness control. In the present invention, wire bar coating is preferably used for the preparation of the hole transport layer, which evenly distributes the solution on the transparent electrode layer through the relative movement of the wire bar and the substrate. Compared with blade coating, wire bar coating can provide finer thickness control and better coating uniformity, thereby significantly improving the photoelectric conversion efficiency of perovskite photovoltaic modules.
[0064] In addition, slot coating can also be used to apply the hole transport layer precursor solution. Slot coating sprays the solution directly onto a moving substrate through a slot nozzle, and can achieve uniform coverage with a very thin coating (e.g., a few hundred nanometers). In the present invention, slot coating can be used as an alternative to prepare a hole transport layer, which is particularly suitable for preparing large-area, uniformly thick films. The parameters of slot coating, such as the distance between the nozzle and the substrate, the solution flow rate, and the substrate movement speed, need to be carefully adjusted to ensure the uniformity of the coating and the precise control of the film thickness.
[0065] In a preferred embodiment, the perovskite layer precursor used in step S3 includes a perovskite crystal with a structure of ABX3, wherein A is CH3NH3, NH2CHNH2, C8H9NH3 or Cs, B is Pb or Sn, and X is Cl, Br, I or a halide. The perovskite layer is a core component of a perovskite solar cell, and its unique structure and excellent photoelectric properties are key factors in the rapid improvement of the efficiency of perovskite solar cells in recent years. In the present invention, the perovskite crystals contained in the perovskite layer precursor solution have a chemical structure of ABX3, wherein the A-position cations generally include methylamine (CH3NH3, MA), formamidine (NH2CHNH2, FA), phenylethylamine (C8H9NH3, PEA) and cesium (Cs). The selection of these cations has an important influence on the band gap, stability and formation kinetics of the perovskite layer. For example, methylamine and formamidine can form perovskite materials with wider band gaps, suitable for absorbing the visible spectrum; while the incorporation of phenylethylamine and cesium can improve the stability of the perovskite material, especially its tolerance to moisture, heat and light. The B-site metal is usually lead (Pb) or tin (Sn). In the present invention, lead is preferably used as the B-site metal, especially Cs x FA 1-x PbI x Br 3-x The structure is preferably a quartz crystal structure, so as to achieve higher photoelectric conversion efficiency and stability. The X-position anion can be chlorine (Cl), bromine (Br), iodine (I) or a combination of their halides. The type and ratio of anions directly affect the photoelectric properties of the perovskite material, such as absorption wavelength, band gap and stability. In the present invention, the performance of the perovskite material is optimized by controlling the ratio of Cs, FA, Pb, I and Br, especially the Cs used in the embodiment. 0.1 FA 0.9 PbI3 exhibits good photoelectric conversion efficiency and stability.
[0066] In a preferred embodiment of the present invention, step S4 also includes forming a modification layer on the electron transport layer by vacuum thermal evaporation after forming the electron transport layer, the modification layer includes one of bathocuproin, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, 4,4'-dicyano-2,2'-biphenyl and 3-(4-tert-butylphenyl)-2-methyl-4,5-dicyano-1,3,4-oxadiazine or any combination thereof, and the coating thickness of the modification layer is in the range of 2nm to 10nm, preferably in the range of 3nm to 8nm. In the preparation process of perovskite solar cells, step S4 not only covers the formation of the electron transport layer, but also includes a process for depositing a fine modification layer on the layer.
[0067] In the present invention, the material of the modification layer may include bathocuproine (BCP), 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (DM-phen), 4,4'-dicyano-2,2'-biphenyl (DNCB) or 3-(4-tert-butylphenyl)-2-methyl-4,5-dicyano-1,3,4-oxadiazine (TBDND). BCP is a widely used interface modification material between the electron transport layer and the subsequent electrode layer in electronic devices such as photovoltaics and organic light-emitting diodes (OLEDs). It can effectively passivate the surface of the electron transport layer, reduce non-radiative recombination centers, thereby improving the mobility and life of electrons and reducing energy loss. The introduction of DM-phen is intended to further optimize the interface characteristics between the electron transport layer and the perovskite layer and improve the collection efficiency of charge carriers. Its organic molecular structure can form a stable interface with perovskite and electron transport layer materials, enhancing the overall charge extraction and transmission capabilities. DNCB and TBDND are selected as components of the modification layer because of their excellent electron transport performance and interface modification capabilities. They can effectively reduce the contact resistance between the electron transport layer and the back electrode layer, while improving the stability of the electron transport layer and resisting the influence of environmental factors (such as humidity and oxygen), thereby extending the service life of the battery.
[0068] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0069] Preparation of hole transport layer precursor solution
[0070] Example 1
[0071] [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid (MeO-2PACz) and n-octylammonium iodide were dissolved in ethanol at a weight ratio of 1:2, and stirred evenly to prepare a hole transport layer precursor solution, the concentration of which was 0.5 mg / ml.
[0072] Example 2-20
[0073] The hole transport layer precursor solutions of Examples 2-20 were prepared in the same manner as Example 1, with the differences listed in Table 1 below.
[0074] Comparative Example 1-2
[0075] The hole transport layer precursor solutions of Comparative Examples 1-2 were prepared in the same manner as in Example 1, with the differences listed in Table 1 below.
[0076] Table 1
[0077]
[0078]
[0079] Preparation of solar cells
[0080] Embodiment 21
[0081] Transparent conductive glass is used as the substrate of the component, with an area of 50×60cm 2 The transparent conductive glass is commercially available FTO conductive glass. Before use, the substrate surface is treated with deionized water, acetone, and isopropanol for 15 minutes in sequence, then cleaned with an ultraviolet light cleaner for 10 minutes, and dried with a nitrogen stream for later use.
[0082] On the transparent conductive substrate dried by nitrogen, a wire rod coating process was used to prepare a hole transport layer. The hole transport layer precursor solution prepared in Example 1 was used as the coating material. The distance between the wire rod and the substrate, i.e., the gap, was 60 μm; the coating speed was 15 mm / s; and the amount of the coating solution was 480 μl. After coating, the substrate was baked in an oven at 100°C for 10 minutes to evaporate the solution to form a hole transport layer.
[0083] The perovskite active layer was prepared on the prepared hole transport layer using a slit coating process, and the thickness of the final perovskite active layer was 450nm. The concentration of the perovskite active layer precursor solution (based on PbI2) used in the slit coating process was 1 mol / ml, the solvent was N,N-dimethylformamide (DMF), and the perovskite crystal structure was Cs 0.1 FA 0.9 After coating, it was baked in an oven at 150°C for 30 minutes to evaporate the solution to form a perovskite active layer.
[0084] The electron transport layer was prepared on the perovskite active layer using a vacuum thermal evaporation process. The thickness of the prepared electron transport layer was 50 nm. The electron transport layer precursor material used was C60. The modification layer was prepared on the electron transport layer using a vacuum thermal evaporation process. The thickness of the prepared modification layer was 6 nm. The modification layer precursor material used was bathocuproin (BCP).
[0085] Finally, a reactive plasma deposition (RPD) device is used to deposit tungsten-doped indium oxide (IWO) on the modified layer as a back electrode layer. The thickness of the back electrode layer is 160 nm.
[0086] Embodiment 22-40
[0087] The solar cells of Examples 22-40 were prepared in the same manner as Example 21, with the differences shown in Table 2 below.
[0088] Comparative Example 3
[0089] Transparent conductive glass is used as the substrate of the component, with an area of 50×60cm 2 The transparent conductive glass is commercially available FTO conductive glass. Before use, the substrate surface is treated with deionized water, acetone, and isopropanol for 15 minutes in sequence, then cleaned with an ultraviolet light cleaner for 10 minutes, and dried with a nitrogen stream for later use.
[0090] On the transparent conductive substrate dried by nitrogen, a wire rod coating process was used to prepare a hole transport layer. The hole transport layer precursor solution prepared in Comparative Example 1 was used as the coating material. The distance between the wire rod and the substrate, i.e., the gap, was 60 μm; the coating speed was 15 mm / s; and the amount of the coating solution was 480 μl. The substrate was then moved into an oven, annealed at 100° C. for 10 minutes, and then taken out and cooled to room temperature to form a hole transport layer.
[0091] The perovskite film layer, electron transport layer and modification layer are sequentially deposited on the substrate obtained above. The perovskite film layer is prepared by slit coating process, and then annealed at 150°C for 30 minutes. The thickness of the perovskite film layer is 450nm; the annealed substrate is moved into the vacuum chamber, and the C60 electron transport layer and the bathocuproin (BCP) modification layer are sequentially prepared by vacuum thermal evaporation. Among them, the C60 evaporation rate is 0.2nm / s, the thickness is 350nm; the BCP evaporation rate is 0.1nm / s, and the thickness is 6nm.
[0092] Finally, a reactive plasma deposition (RPD) device is used to deposit tungsten-doped indium oxide (IWO) on the modified layer as a back electrode layer. The thickness of the back electrode layer is 160 nm.
[0093] Comparative Example 4
[0094] The solar cell of Comparative Example 4 was prepared by the same method as Comparative Example 3, and the differences are shown in Table 2 below.
[0095] Testing the conversion efficiency of solar cells
[0096] According to the national standard 20230664-T-339, the photoelectric conversion efficiency of the solar cells prepared in Examples 21-40 and Comparative Examples 3-4 was tested under standard test conditions. The test results are shown in Table 2 below.
[0097] Table 2
[0098] Hole transport layer precursor solution Conversion efficiency (%) Embodiment 21 Example 1 15.8 Embodiment 22 Example 2 16.8 Embodiment 23 Example 3 15.4 Embodiment 24 Example 4 16.9 Embodiment 25 Example 5 15.7 Embodiment 26 Example 6 16.3 Embodiment 27 Example 7 15.9 Embodiment 28 Example 8 16.8 Embodiment 29 Example 9 16.0 Embodiment 30 Example 10 17.1 Embodiment 31 Embodiment 11 16.2 Embodiment 32 Example 12 17.4 Embodiment 33 Embodiment 13 16.3 Embodiment 34 Embodiment 14 17.5 Embodiment 35 Embodiment 15 16.6 Embodiment 36 Example 16 17.7 Embodiment 37 Embodiment 17 16.4 Embodiment 38 Embodiment 18 17.0 Example 3 Embodiment 19 16.6 Embodiment 40 Embodiment 20 17.8 Comparative Example 3 Comparative Example 1 15.6 Comparative Example 4 Comparative Example 2 16.0
[0099] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0100] In the embodiment, the weight ratio of MeO-2PACz or Me-4PACz to organic iodine ammonium salt (n-octyl ammonium iodide, PEAI and its derivatives) varies in the range of 1:2 to 2:1, which has a significant effect on the photoelectric conversion efficiency of the perovskite photovoltaic module. Taking the ratio of MeO-2PACz and n-octyl ammonium iodide as an example (Examples 21 to 23), when the ratio is 1:1 (Example 22), the photoelectric conversion efficiency of the solar cell reaches 16.8%, which is higher than 15.6% in Comparative Example 3 and the results when the ratio is 1:2 or 2:1 (Examples 21 and 23). This shows that a mixture of a specific ratio can form better interface properties and charge transfer properties in the hole transport layer, thereby improving battery performance.
[0101] Through Examples 25 to 39, we can see that when MeO-2PACz or Me-4PACz is combined with different organic ammonium iodide salts (PEAI and fluorinated derivatives), the photoelectric conversion efficiency of the solar cell also shows obvious differences. In particular, when mixed with 4-fluorophenethyl iodide ammonium (pF-PEAI) to prepare the hole transport layer (Examples 30 to 32), the photoelectric conversion efficiency reached 17.1%, 17.4% and 16.2%, respectively, which is higher than that of Comparative Examples 3 and 4 without adding organic ammonium iodide salts. This shows that the substitution of fluorine atoms can optimize the electronic structure of the hole transport layer, improve its interface contact with the perovskite layer, and thus improve the photoelectric conversion efficiency of the battery.
[0102] The examples and comparative examples all use wet processing technology to prepare the hole transport layer, including spin coating, wire rod coating, etc., but the results show that the wire rod coating process (used in the examples) is particularly effective for the hole transport layer precursor solution proposed in the present invention, and can achieve large-area uniform coating, which is conducive to the large-scale preparation of components. Compared with the spin coating process using only MeO-2PACz or Me-4PACz solution (Comparative Examples 1 and 2), wire rod coating combined with the hole transport layer precursor solution of the present invention significantly improves the photoelectric conversion efficiency of solar cells.
[0103] By combining the optimized hole transport layer (containing MeO-2PACz or Me-4PACz and organic iodine ammonium salt) with the subsequent perovskite layer, electron transport layer (C60), modification layer (BCP) and back electrode layer (IWO), the embodiment shows the positive effect of cross-layer synergy. For example, in Example 16, the hole transport layer prepared by mixing Me-4PACz and mF-PEAI in a 1:1 weight ratio, plus the C60 electron transport layer, BCP modification layer and IWO back electrode, the photoelectric conversion efficiency of the final component reached 17.7%, which is higher than the efficiency of the solar cells prepared in all comparative examples, confirming the significant advantages of the present invention in improving the efficiency of perovskite cells.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A hole transport layer precursor solution, characterized in that: The invention comprises a carbazole hole transport material, an organic iodine ammonium salt and a solvent, wherein the organic iodine ammonium salt is selected from alkyl ammonium iodide and / or aromatic iodine ammonium.
2. The hole transport layer precursor solution according to claim 1, characterized in that: The carbazole hole transport material includes one of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphoric acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid, 4-cyano-3,6-di(4-cyanophenyl)-9H-carbazole, 4,4'-diamino-2,2'-bicarbazole and 4,4',4"-tri(methylcyclohexyl)-triphenylamine or any combination thereof.
3. The hole transport layer precursor solution according to claim 1, characterized in that: The alkyl ammonium iodide includes a straight-chain alkyl ammonium iodide of 4 to 15 carbon atoms; preferably, the alkyl ammonium iodide includes one of n-butyl ammonium iodide, n-pentyl ammonium iodide, n-hexyl ammonium iodide, n-octyl ammonium iodide, n-decyl ammonium iodide, n-dodecyl ammonium iodide, n-tetradecyl ammonium iodide and n-hexadecyl ammonium iodide, or any combination thereof.
4. The hole transport layer precursor solution according to claim 1, characterized in that: The aromatic iodinated amine includes substituted or unsubstituted phenyl iodinated amine; preferably, the aromatic iodinated amine includes phenyl iodinated amine, 4-fluorophenyl iodinated amine, 3-fluorophenyl iodinated amine, 2-fluorophenyl iodinated amine, 4-cyanophenyl iodinated amine, 4-methylphenyl iodinated amine, 4-ethylphenyl iodinated amine, phenethyl iodinated amine, 4-fluorophenethyl iodinated amine, 3-fluorophenethyl iodinated amine, 2-fluorophenethyl iodinated amine, 4-chlorophenethyl iodinated amine and 4-methoxyphenethyl iodinated amine or any combination thereof.
5. The hole transport layer precursor solution according to claim 1, characterized in that: The weight ratio of the carbazole hole transport material to the organic iodine ammonium salt is between 1:10 and 10:1, preferably between 1:4 and 4:1, and more preferably between 1:2 and 2:
1.
6. The hole transport layer precursor solution according to claim 1, characterized in that: The solvent is selected from one of methanol, ethanol, isopropanol, n-propanol, butanol, ethylene glycol, ethyl acetate, ethyl propionate, acetone, methyl ethyl ketone, acetonitrile, propionitrile, toluene, xylene, dimethylformamide and dimethyl sulfoxide, or any combination thereof.
7. The hole transport layer precursor solution according to claim 1, characterized in that: Based on the total volume of the solvent in the hole transport layer precursor solution, the total concentration of the carbazole hole transport material and the organic iodine ammonium salt is in the range of 0.1 mg / ml to 1 mg / ml, preferably in the range of 0.2 mg / ml to 0.8 mg / ml.
8. A solar cell, characterized in that: Includes the following layers: A transparent electrode layer; hole transport layer; Perovskite layer; Electron transport layer; as well as Back electrode layer, The hole transport layer is prepared from the hole transport layer precursor solution according to any one of claims 1 to 7.
9. A method for preparing the solar cell according to claim 8, characterized in that: The following steps are involved: Step S1, dissolving a carbazole hole transport material and an organic iodine ammonium salt in a solvent to obtain a hole transport layer precursor solution; Step S2, coating the hole transport layer precursor solution on the transparent electrode layer using a wet processing technology to obtain a hole transport layer; Step S3, preparing a perovskite layer on the hole transport layer; Step S4, preparing an electron transport layer on the perovskite layer; Step S5, preparing a back electrode layer on the electron transport layer.
10. The method according to claim 9, characterized in that The wet processing technology is blade coating, wire rod coating or slot coating.
11. The method according to claim 9, characterized in that The hole transport layer precursor solution is coated on the transparent electrode layer using wire bar coating, and the coating thickness of the hole transport layer is in the range of 10 μm to 200 μm, preferably in the range of 30 μm to 120 μm; the coating speed is in the range of 2 mm / s to 50 mm / s, preferably in the range of 3 mm / s to 20 mm / s.
12. The method according to claim 9, characterized in that The step S3 further includes applying a perovskite layer precursor onto the hole transport layer using slit coating, wherein the perovskite layer precursor includes a perovskite crystal with a structure of ABX3, wherein A is CH3NH3, NH2CHNH2, C8H9NH3 or Cs, B is Pb or Sn, and X is Cl, Br, I or a halide; the coating thickness of the perovskite layer is in the range of 200nm to 1000nm, preferably in the range of 300nm to 600nm.
13. The method according to claim 9, characterized in that The step S4 further comprises forming an electron transport layer precursor on the perovskite layer by vacuum thermal evaporation, wherein the electron transport layer precursor comprises one of fullerene, titanium dioxide, zinc oxide, tin oxide and zirconium oxide or any combination thereof, and the coating thickness of the electron transport layer is in the range of 10 nm to 100 nm, preferably in the range of 3 nm to 80 nm, Preferably, step S4 further comprises, after forming the electron transport layer, forming a modification layer on the electron transport layer by vacuum thermal evaporation, wherein the modification layer comprises one of bathocuproin, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, 4,4'-dicyano-2,2'-biphenyl and 3-(4-tert-butylphenyl)-2-methyl-4,5-dicyano-1,3,4-oxadiazine or any combination thereof, and the coating thickness of the modification layer is in the range of 2nm to 10nm, preferably in the range of 3nm to 8nm.
14. The method according to claim 9, characterized in that The step S4 further includes depositing tungsten indium oxide on the electron transport layer by a reactive plasma deposition process to form the back electrode layer, and the coating thickness of the back electrode layer is in the range of 100 nm to 300 nm, preferably in the range of 120 nm to 200 nm.
Citation Information
Cited By
Perovskite solar cell, preparation method thereof and photovoltaic module
CN120500195A